Reviving Ophelia : saving the selves of adolescent girls - Pipher, Mary Bray. (New York : Ballantine Books, 1995)
Looks at the problems and pressures facing adolescent girls, and suggests how to help them develop into self-assured young adults.
Includes bibliographical references (p. [295]) and index.
Adult
Adult
Library Journal Starred
Kliatt
900L
Keywords: Teenage girls -- Psychology -- Case studies; Teenage girls -- Family relationships -- Case studies; Self-esteem in adolescence -- Case studies; Adolescent psychology -- Case studies; Teenagers -- Psychology -- Case studies; Self-esteem -- Psychological aspects -- Case studies